Pengembangan Spiritualitas Remaja: Mengapa Remaja Laki-Laki Lebih Memerlukan Dukungan Keluarga Dalam Pengembangan Spiritualitas - Mangestuti, Retno; Aziz, Rahmat (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2017)
This study aimed to examine the influence on family support for adolescent spirituality. Subjects were 167 students at four universities in Malang. Data were collected by family support scale and daily spiritual experiences scale. The results showed that family support influence on spirituality of R = .356 p.50. Psychological support was a significant factor influencing on adolescent spirituality.